2015
DOI: 10.1186/s12906-016-0990-7
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antibiotic-modifying activities of three food plants (Xanthosoma mafaffa Lam., Moringa oleifera (L.) Schott and Passiflora edulis Sims) against multidrug-resistant (MDR) Gram-negative bacteria

Abstract: BackgroundThe present study was designed to investigate the antibacterial activities of the methanol extract of three edible plants, namely Xanthosoma mafaffa, Moringa oleifera and Passiflora edulis and their synergistic effects with some commonly used antibiotics against MDR Gram-negative bacteria expressing active efflux pumps.MethodsBroth microdilution method was used to determine the minimum inhibitory concentrations (MICs) and the minimum bactericidal concentrations (MBCs) of the extracts, as well as thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 36 publications
3
50
1
Order By: Relevance
“…The experiments carried out by Daotam et al(2016) confirmed that the methanol extract of M. oleifera leaves showed different inhibition patterns against different bacterial strains including E. coli, E. aerogenes, K. pneumoniae and P. aeruginosa. Abdalla and Abdelgadir, (2016) reported that water and methanol extracts of M. chamomilla showed different degrees of antibacterial activities against bacteria, including P. aeruginosa, S. aureus, B. cereus and E. coli.…”
Section: Discussionmentioning
confidence: 75%
“…The experiments carried out by Daotam et al(2016) confirmed that the methanol extract of M. oleifera leaves showed different inhibition patterns against different bacterial strains including E. coli, E. aerogenes, K. pneumoniae and P. aeruginosa. Abdalla and Abdelgadir, (2016) reported that water and methanol extracts of M. chamomilla showed different degrees of antibacterial activities against bacteria, including P. aeruginosa, S. aureus, B. cereus and E. coli.…”
Section: Discussionmentioning
confidence: 75%
“…The biological activity of moringin extracts and moringin itself attracted the attention of a number of researchers in different areas. This phyto-compound possesses in fact a wide range of biological activities, including antioxidant [8], antimicrobial [9], antibacterial [6], antifungal and antiviral [10][11][12], and deterrent effects towards some insects. [13].…”
Section: Moringa Oleifera Lam a Multi-purpose Treementioning
confidence: 99%
“…Numerous investigations have recommended that different extracts from various tissues of M. oleifera showed antibacterial properties against both gram‐negative and gram‐positive bacteria viz., fresh leaf juice against Pseudomonas aeruginosa and Staphylococcus aureus (Caceres, Cabrera, Morales, Mollinedo, & Mendia, ); aqueous leaf extract against S. aureus , Vibrio cholerae , and Escherichia coli (Vieira, Mourao, Angelo, Costa, & Vieira, ); methanol extract of leaves against 13 different bacterial strains tested, including E. coli , Enterobacter aerogenes , Klebsiella pneumonia , P. aeruginosa , and Providencia stuartii (Dzotam et al, ); ethanol extracts of foliages and seeds against Trichophyton rubrum , T. mentagrophytes , Epidermophyton floccosum , and Microsporum canis (Chuang et al, ); chloroform and ethanol extracts of seeds and foliage against E. coli , P. aeruginosa , S. aureus , and E. aerogenes (Bukar, Uba, & Oyeyi, ); chloroform extract of flowers and ethanol extract of pods against V. cholera , V. vulnificus , and V. mimicus (Brilhante et al (); water‐soluble seed lectin against S. aureus and E. coli (Ferreira et al, ); phenolics rich extract of seed flour against Bacillus cereus , S. aureus , E. coli , and Yersinia enterocolitica (Govardhan‐Singh, Negi, & Radha, ); hexane, petroleum ether, butanol, chloroform, acetone, ethyl acetate, methanol, and water extracts of pod husk against S. aureus , S. epidermidis , Salmonella typhimurium , E. coli , and K. pneumonia (Arora & Onsare, ); acetone extract of foliage against S. aureus , Enterococcus faecalis , E. coli , P. aeruginosa , Candida albicans , Aspergillus fumigates , and Cryptococcus neoformans (Ratshilivha, Awouafack, du Toit, & Eloff, ); aqueous, methanol and ethyl acetate extracts of seeds against E. coli , K. pneumoniae , Proteus mirabilis , P. aeruginosa , and S. aureus (Emmanuel et al, ); ethyl acetate extract of bark against S. aureus , Citrobacter freundii , B. megaterium , and P. fluoescens (Zaffer et al, ); flavonoids extract of seeds against S. aureus , P. aeruginosa , and C. albicans (Onsare & Arora, ).…”
Section: Resultsmentioning
confidence: 99%